Eletrólito sólido β/β”-alumina para protótipo de bateria sódio-níquel - Nonemacher, Juliane Franciele (Universidade Federal de São Carlos, 2014)
Itaipu Binational along with the Swiss company power generation Kraftwerke Oberhasli AG/KWO, are developing a battery of nickel-sodium salt (Na/NiCl2), which uses β/β"-Al2O3 ceramic as solid electrolyte, to apply on electric vehicles and stationary banks. The main challenges in obtaining β/β"-alumina are obtain more content β"-Al2O3 phase, the difficulty in controlling the sodium loss during the sintering and minimize abnormal grain growth which leads to a duplex microstructure which compromises the mechanical strength. This paper aims to: i) develop ceramic solid electrolyte β/β "-alumina using powders prepared by citrate process (CP) and mixed oxides process (MOP) and correlate the microstructure with electrical conductivity and mechanical properties, ii) obtain solid electrolyte tubular using the powder which generated the best samples. The samples obtained with MOP powder were not sensitive to sintering atmosphere. The amount of β” phase was ≈75%, microstructure obtained was duplex form containing larger grains (≈150 μm) dispersed in a matrix of smaller grains (≤5 μm). The higher mechanical resistance value to radial compression was 92 ± 14 MPa and the maximum the electrical conductivity value was 1.03x10-1 S.cm-1 at 300 oC. Citrate process produced nano-powder, which was more sensitive to the samples stowage during sintering and generated a microstructure more thin and homogeneous with grain size about ≤5 μm. Amount of β” phase, electrical conductivity and mechanical strength were lower than those obtained by the MOP. The solid electrolytes tubular were obtained by isostatic pressing with powder prepared via MOP. The pipes have a good mechanical resistance to green body for handling and finishing with good densification after sintering, indicating the viability of manufacturing of tubes for batteries.
Solid electrolyte β/β”-alumina for sodium-niquel battery prototype
Keywords: Cerâmica; Eletrólito sólido; Microestrutura; Processamento cerâmico; Protótipo tubular; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA